Choices for competing service providers with heterogeneous customers: Traditional versus opaque sales modes. (January 2021) - Feng, Bo; Mao, Zhaofang; Li, Hui
Highlights: Opaque channel selection problem is integrated with revenue sharing contract design. Whether two competing service providers should collaborate with an intermediary when facing heterogeneous customers are discussed. Styled models are built to derive the optimal decision on opaque channel selection for the competing service providers. Useful managerial implications on the conditions of opaque channel selection are provided. Abstract: Competing service providers have been conducting opaque sales widely by cooperating with an intermediary, such as Priceline.com and Hotwire.com, to increase capacity flexibility, realise price discrimination and create a new channel for customers. Whether competing service providers should collaborate with an intermediary when facing heterogeneous customers and how a contract design can be made between service providers and the intermediary are two challenging research problems. Recent advances in opaque sales have focused on homogeneous customers, whereas the revenue sharing mechanism for heterogeneous customers has remained unexplored. This study considers two competing service providers that collaborate with an intermediary in a heterogeneous market with leisure and business customers. Styled models are built to capture the traditional and opaque sales modes. The contracting strategies are derived by comparing the profit of the two modes. Considering the simultaneous arrivals of two kinds of customers, we find that the decisions of service providers relate to two factors: the market structure and the revenue sharing mechanisms. In a high-pricing strategy market, service providers may collaborate with an intermediary. Conversely, in a low-pricing strategy market, service providers may not collaborate with an intermediary. In both situations, service providers should strive for a balance between the profit derived from the intermediary and the potential profit loss from opaque sales.